EFFECT OF REPETITIVE WELDING USING ORBITAL GMAW ON TENSILE PROPERTIES OF AISI 304 AUSTENITIC STAINLESS STEEL PIPES - Hussein, Nur Izan Syahriah binti (JEMIS (Journal of Engineering & Management in Industrial System), 2020)
Repair welding is often carried out in steel structural components. The main intention of repair welding is by providing a cure for existing welding defects during initial stages or weld deterioration during their services that can increase the service lives or performance of components. Repair welding is a better choice as compared to replacing the parts because it is a more economical, faster and reliable method to make a part come back to its services when failure of the parts is identified. In this study, the effect of welding parameters on tensile properties of AISI 304 austenitic stainless steel pipes was investigated. The best set of parameters was suggested by using Taguchi method as the design of experiment and analysis. Results showed that the optimum set of parameters for achieving highest ultimate tensile strength (UTS) values was when arc current, arc voltage and welding at 160 A, 22 V and 50 mm/min, respectively. On the other hand, the optimum set of parameters for achieving highest elongation percentage was when arc current, arc voltage and welding speed at 160 A, 22 V and 40 mm/min. Based on the optimum set of parameters, the repetitive welding to replicate a repairing process was performed. It was evidenced that the UTS showed an increasing trend up to the second repair (RW2) before decreased after the third repair (RW3). The highest value of UTS obtained at second repair (RW2) was 525.51 MPa. The repair welding has caused dynamic changed in the microstructure of the weldment. Therefore, the number of optimum repetitions for the AISI 304 austenitic stainless steel pipes was proposed up to second repair.